2013
DOI: 10.1016/j.ultrasmedbio.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Trapped Surface Bubbles as the Cause for the Twinkling Artifact in Ultrasound Imaging

Abstract: The mechanism of the twinkling artifact (TA) that occurs during Doppler ultrasound imaging of kidney stones was investigated. The TA expresses itself in Doppler images as time-varying color. To quantitatively define the TA, beamforming and Doppler processing were performed on raw per-channel radio-frequency (RF) data collected when imaging human kidney stones in vitro. Suppression of twinkling by an ensemble of computer generated replicas of a single RF received signal demonstrated that the TA arises from vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 33 publications
2
45
1
4
Order By: Relevance
“…The threshold and color priority was defined the same way as in Lu et al . [20]: the background noise level, defined as the average of the Doppler powers over all pixels in the image, multiplied by a factor of two. The color encoding priority was set to the highest level so that color pixels are plotted prioritized than grey scale pixels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold and color priority was defined the same way as in Lu et al . [20]: the background noise level, defined as the average of the Doppler powers over all pixels in the image, multiplied by a factor of two. The color encoding priority was set to the highest level so that color pixels are plotted prioritized than grey scale pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, color Doppler, a method normally used to image moving scatterers in tissue, such as red blood cells, was also found to be sensitive to bubbles trapped in the cracks and crevices of solid concretions in soft tissues (e.g. kidney stones, calcifications or edges of medical instruments) [20]. Crevice bubbles have been shown to give rise to the so-called twinkling artifact (TA) - a dynamic color mosaic on the image of a hard concretion in the color Doppler ultrasound display [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Lu et al (13) suggested that twinkling artifact could be generated by the interaction of sound waves with micro air bubbles trapped at the surface of the stone. The AEI-High MI mode uses high intensity ultrasound waves to detect bubbles for loss of correlation (LOC) imaging.…”
Section: Aei-high MI Ultrasound Mode For the Diagnosis Of Urolithiasismentioning
confidence: 99%
“…LOC imaging, also known as sonoscintigraphy or stimulated acoustic emission and transient scattering uses an ultrasound pulse which is powerful enough to destroy the bubbles and produces a strong backscatter echo (14). The hypothesis of the destruction of trapped air bubbles suggested by Lu et al (13) could be a possible explanation of the scintillation artifact; however, it might not be the only reason why the artifact is visible only on AEI-High MI mode and not on B-mode gray-scale imaging. In our study, the mechanical index values for gray-scale imaging and AEI-High MI mode imaging were recorded and were between 1.1-1.4 for gray-scale imaging and between 1.13-1.4 for AEI-High MI.…”
Section: Aei-high MI Ultrasound Mode For the Diagnosis Of Urolithiasismentioning
confidence: 99%
“…Ultrasound Doppler techniques are normally used to image moving scatterers in blood vessels, such as red blood cells and UCAs, and they can also detect bubbles trapped in the cracks and crevices of solid concretions in soft tissues (Lu et al 2013). Therefore, Li et al (2014) hypothesized that Doppler techniques could be used to detect cavitation bubbles induced by pulsed HIFU, and they obtained preliminary results in tissue-mimicking gel phantoms.…”
Section: Bubble Doppler Technique For Cavitation Imagingmentioning
confidence: 99%